2020
DOI: 10.1038/s41598-020-70627-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers and continuity of healthy metabolic status: Tehran cardio-metabolic genetic study (TCGS)

Abstract: obese individuals can be categorized as "healthy obese" (MHo) and "unhealthy obese" (MUo) based on the presence or absence of metabolic abnormality. this study sets out to assess potential genetic causes behind persistence of healthy metabolic status in individuals categorized as "healthy obese". This study was conducted in the framework of the Tehran cardio-metabolic genetic study (TCGS). 766 MHO subjects at the start of the study followed up 15 years for occurrence of metabolic unhealthy status. these two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previous characterization of metabolically healthy obese individuals determined that maintained health with obesity corresponded with upregulated mitochondrial oxidative phosphorylation and fatty acid oxidation transcript expression, decreased levels of markers of chronic inflammation, and reduced liver adipose accumulation [ 21 ]. Additionally, expression of SLC39A8 and SLC16A7 , solute carrier family members, in circulation or saliva were associated with maintained metabolic health in obese women [ 22 , 23 ]. Our work verifies these findings and adds vital information regarding differences in local immune cell populations in healthy and unhealthy obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous characterization of metabolically healthy obese individuals determined that maintained health with obesity corresponded with upregulated mitochondrial oxidative phosphorylation and fatty acid oxidation transcript expression, decreased levels of markers of chronic inflammation, and reduced liver adipose accumulation [ 21 ]. Additionally, expression of SLC39A8 and SLC16A7 , solute carrier family members, in circulation or saliva were associated with maintained metabolic health in obese women [ 22 , 23 ]. Our work verifies these findings and adds vital information regarding differences in local immune cell populations in healthy and unhealthy obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 31 polymorphisms were observed to be located close to at least one other SNP within the same gene or intergenic region, suggesting their special relevance according to the authors. A different study reported a significant association of FTO (rs1121980) and TCF7L2 (rs7903146) genetic variants with maintaining metabolic health in obese women, who did not develop MetS according to joint interim statement criteria[ 27 ]. In addition, a genetic variant of SLC39A8 (rs13107325) was found to have a statistically significant association with metabolic health status in a subgroup of postmenopausal women.…”
Section: Genomicsmentioning
confidence: 99%